The use of information technology applications in the provision of health care to a COVID-19 patients - Ihsan Ali Hassan; Ahmed Adnan Mohammed Al-Azzawi; Mohammed Layth Talal (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
At the time of writing this study, the COVID-19 virus continues to spread through its multiple mutants, the latest of which is (Omicron). Therefore, it was necessary to use effective and unconventional treatments to reduce the spread of this virus and to deliver health care to its infected without the need to be exposed to the risk of infection. This research paper presents valuable solutions for communicating with COVID-19 patients through the use of information technology applications. This method contributes to reducing the consumption of medical resources, reducing contact with patients, and helping with social distancing, which contributes to reducing the spread of this virus. The process of using information technology means to provide medical advice and treatment to patients by telemedicine doctors has been clarified. More importantly, the results of this study presented the factors affecting the use of these applications in terms of social, technological, and organizational.